A preliminary study of the moss genus Isopterygium in Latin America A preliminary study of the moss genus Isopterygium in Latin America - Ireland Robert R. (Caldasia)
Se presenta el estudio taxonómico preliminar del género Isopterygium (Hypnaceae), musgo pleurocárpico, en Latinoamérica. Se localizaron y examinaron 78 ejemplares tipo de los 92 taxa reconocidos, de acuerdo con el Index Muscorum, para México, Centro y Sur América. El detallado estudio nomenclatural permitió reconocer para la región siete especies: Isopterygium affusum Mitt., I. byssobolax (C. Müll.) Par, I. miradoricum (C. Müll.) Jaeg. & Sauerb, I. subbrevisetum (Hampe) Broth., I. sobglobosum Herz., I. tenerifolium Mitt. e I. tenerum (Sw.) Mitt. Se provee una clave para la identificación de las especies, su distribución conocida y la lista de sinónimos para cada una de ellas.  Algunos taxa anteriormente ubicados en Isopterygium fue necesario transferirlos a otros taxa, lo cual requiere las siguientes combinaciones nuevas: Wijkia alstonii (Bartr.) Irel. (Isopterygium alstonii Bartr.), Pseudotaxiphyllum homomallifolium (Redf.) Irel. (Isopereygium homomallifolium Redf.), Pseudotaxiphyllum machrisianum (Crum) Irel. (Taxiphyllum machrisianum Crum), Pseudotaxiphyllum richardsii (Bartr.) Irel. (Isopterygium richardsii Bartr.) A preliminary taxonomic study was conducted on the pleurocarpous moss genus Isopterygium in Latin America. The types of 78 the 92 taxa recognized for Mexico, Central and South America by Index Muscorum were located and examined. Synonymy was found to be extensive with only seven species presently being recognized for the region, including Isopterygium affusum Mitt., I. byssobolax (C. Müll.) Par .. I. miradoricum (C. Müll.) Jaeg. & Sauerb., I. subbrevisetum (Hampe) Broth., I. subglobosum Herz., I. tenerifolium Mitt. and I. tenerum (Sw.) Mitt. A key to the identification of the species, their known distribution and a list of synonyms for each species is provided. It was necessary to transfer some of the taxa formerly placed in Isopterygium into other genera which required the following new combinations: Wijkia alstonii (Bartr.) Irel. (Isopterygium alstonii Bartr.) , Pseudotaxiphyllum homomallifolium (Redf.) Irel. (Isopterygium homomallifolium Redf.), Pseudotaxiphyllum machrisianum (Crum) Irel. (Taxiphyllum machrisianum Crum), Pseudotaxiphyllum richardsii (Bartr) Irel. (Isopterygium richardsii Bartr.).